Viral-like brain inflammation during development causes increased seizure susceptibility in adult rats - M.A. Galic; K. Riazi; A.K. Henderson; S. Tsutsui; Q.J. Pittman (Neurobiology of Disease, 2009)
Viral infections of the CNS and their accompanying inflammation can cause long-term neurological effects, including increased risk for seizures. To examine the effects of CNS inflammation, we infused polyinosinic:polycytidylic acid, intracerebroventricularly to mimic a viral CNS infection in 14 day-old rats. This caused fever and an increase in the pro-inflammatory cytokine, interleukin (IL)-1β in the brain. As young adults, these animals were more susceptible to lithium-pilocarpine and pentylenetetrazol-induced seizures and showed memory deficits in fear conditioning. Whereas there was no alteration in adult hippocampal cytokine levels, we found a marked increase in NMDA (NR2A and C) and AMPA (GluR1) glutamate receptor subunit mRNA expression. The increase in seizure susceptibility, glutamate receptor subunits, and hippocampal IL-1β levels were suppressed by neonatal systemic minocycline. Thus, a novel model of viral CNS inflammation reveals pathophysiological relationships between brain cytokines, glutamate receptors, behaviour and seizures, which can be attenuated by anti-inflammatory agents like minocycline.